The Effectiveness of Digital Media in Teaching Orchestration: A Case Study of Sibelius - Dewi, Vivi Ervina; Suwahyono, Agus; Kristiandri, Dhani; Dianita, Jihan Mutiara; Indyana, Luth (Gondang: Jurnal Seni dan Budaya, 2025)
Orchestration is one of the theoretical courses conducted in 4th semester at the Music Study Programme, Faculty of Language and Arts, Universitas Negeri Surabaya. However, in its implementation there are still obstacles and problems. The ability of one student to another in orchestrating songs is very different. The inequality is shown when students work on assignments to orchestrate songs given by lecturers during the midterm and final exams. The work on the task obtained significantly different results. The obstacles and problems that exist in the orchestration lecture process cause a great influence on the development of student abilities. This research tries to present a treatment through learning tools in the form of sibelius software. This research is intended to test the effectiveness of learning tools in the form of Sibelius software in orchestration courses. The research method used is a quantitative method with the type of quasi experiment. The experimental design used in this study was pretest-posttest control group design. The results of the paired sample t test in the experimental group and control group at posttest with a significance value in the Sig column of 0.011 and 0.005. The significance value shows <0.05, so it can be said that there is a difference in the pretest results of the skills and knowledge of orchestrating student songs between the experimental group and the control group. Therefore, it can be concluded that there is a significant difference in the skills and knowledge of orchestrating songs between students who are taught using a stave book and students who are taught using sibelius software in the Music Study Programme. Thus, the use of sibelius software in orchestration lectures is said to be effective. However, because this study used a quasi-experimental type, there are internal and external factors that affect the improvement of students' skills and knowledge in orchestrating songs, such as individual student motivation and musical experience.